The 4-step Early Research Exposure Model: Fostering Research Acumen in Undergraduate Medical Students - Anita S Chalak; Yogesh R Pawade; Shivaji S Chalak; Kinjalka Ghosh (Indian Journal of Medical Biochemistry)
Introduction: Integrating research into undergraduate (UG) medical education is crucial for cultivating a new generation of physician-scientists capable of addressing complex health challenges. This study aimed to develop and evaluate the 4-step Early Research Exposure (ERE) Model, which provides a structured framework to introduce students to research, nurture their skills, and inspire them to pursue research-oriented careers. Aim and objectives: The study sought to develop the ERE Model and assess its acceptability and feasibility among medical students, hypothesizing that its implementation would enable students to acquire the necessary knowledge, skills, and motivation to become future leaders in biomedical research. Methodology: This prospective, single-blind, randomized, interventional study was conducted over 3 years at a medical college in India. All Phase-I MBBS students who consented were included and randomly assigned to either a control or intervention group. The intervention group was exposed to the 4-step ERE Model, comprising sessions on research introduction, reading and analysis, researcher interaction, and hands-on projects. Quantitative and qualitative data were collected using a validated questionnaire and focus group discussions (FGD) to assess students’ perceptions and knowledge gain. Results: A total of 184 students participated, with a response rate of 92%. The intervention group exhibited a significant improvement in research knowledge and attitudes, as evidenced by the substantial increase in posttest scores compared to the control group. The Class-Average Absolute Learning Gain, Class-Average Relative Learning Gain, and Class-Average Normalized Gain metrics further substantiated the model's effectiveness in fostering research acumen. Qualitative analysis of student and faculty feedback revealed a highly positive reception of the ERE Model, with participants highlighting its relevance, importance, and potential for future research preparation. Conclusion: The 4-step ERE Model has demonstrated its potential as a powerful tool for cultivating research skills and inspiring UG medical students to pursue careers in biomedical research. By addressing identified challenges and expanding its implementation, the ERE Model can contribute to the advancement of medical science and improve patient care.